The state and consideration for skin test of β-lactam antibiotics in pediatrics - Gao, Chunhui; Ma, Bowen; Liu, Wei; Zhu, Liqin (Frontiers in Cellular and Infection Microbiology, 2023)
β-lactam antibiotics are the most frequently used drugs and the most common drugs that cause allergic reactions in pediatrics. The occurrence of some allergic reactions can be predicted by skin test, especially severe adverse reactions such as anaphylactic shock. Thus, Penicillin and cephalosporin skin test is widely used to predict allergic reactions before medication in pediatrics. However, false positive results of skin test were more often encountered in pediatrics than in adults. In fact, most children who are labeled as β-lactam allergic are not allergic to the antibiotic, resulting in the use of alternative antibiotics, which are less effective, more toxic, more expensive, and can contribute to increased drug-resistant. There has been controversy over whether β-lactam antibiotics should be tested for skin allergy before application in children. Based on the great controversy in the implementation of β-lactam antibiotics skin test, especially the controversial cephalosporin skin test in pediatrics, the mechanism and reasons of anaphylaxis to β-lactam antibiotics, the significance of β-lactam antibiotics skin test, current state of β-lactam antibiotics skin test at home and abroad and the problems of domestic and international skin test were analyzed to determine a unified standard of β-lactam antibiotics skin test in pediatrics, in order to prevent and decrease adverse drug reactions, avoid waste of drugs and a large amount of manpower and material resource consumption.